Working capital, treasury management and company valuation - Genoni, Gustavo; Zurita L., Salvador (Estudios de Administración, 2004)
In the professional practice, the concept of operational working capital is confused with the accounting definition of working capital, with consequent errors both in the treasury of companies, and in the valuation of companies. In this paper we discuss the important distinction between operational working capital (a characteristic of a business) and the accounting concept of working capital (a financial decision). Also, we challenge the popular view that suggests that firms should finance with long term debt the recurrent portion of their operative working capital, discussing both the implicit costs and risks of such a strategy. Finally, taking the accounting definition of working capital for the operational working capital can lead also to important mistakes in valuation of companies. One of such too frequent mistake is to subtract only the long term debt from the present value of free cash flows to obtain an estimate of the economic value of equity, with a consequent overestimation of its value.